Efficacy of a single ultrasound-guided injection of high molecular weight hyaluronic acid combined with collagen tripeptide in patients with knee osteoarthritis and chondrocalcinosis - Porta, Francesco; Filippucci, Emilio; Cipolletta, Edoardo; La Grua, Marco; Barni, Xenia; Sirotti, Silvia; Vreju, Florentin Ananu (Frontiers in Medicine, 2024)
Introduction Osteoarthritis (OA) and calcium pyrophosphate deposition (CPPD) often co-exist, this resulting in a clinical condition characterized by amplified inflammation and more severe and faster cartilage degeneration compared to OA alone. Our study aims to explore the efficacy of a therapeutic approach that addresses both conditions, using a combination of a high molecular weight hyaluronic acid (HMWHA) and collagen tripeptide (CTP). Additionally, safety profile and baseline characteristic predictive value were evaluated. Methods We conducted a retrospective study on patients diagnosed with symptomatic knee OA (KOA) and CPPD treated by ultrasound (US) guided intraarticular injections of HMWHA-CT in the outpatient clinics of the Interdisciplinary Pain Medicine Unit at Santa Maria Maddalena Hospital, Occhiobello, Italy and in the Rheumatology Unit of the Emergency County Hospital Craiova, Romania (ECH Craiova). All the patients underwent clinical and US evaluation at baseline, 1, 3, and 6 months. From clinical point of view, Numeric Rating Scale (NRS) pain and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) were recorded. US data included detection of synovitis, cartilage damage, osteophytes, and CPPD deposits. Clinical efficacy was defined with NRS and WOMAC variations in respect to baseline and using the minimal clinically important difference values: an improvement of 2 point for NRS pain and 10 for the total score for WOMAC. Results Twenty-nine patients (34 knees) were injected and evaluated. Overall pain levels, as measured by NRS, demonstrated a consistent decrease in patients across all follow-up intervals, with the most substantial improvement at the 6-month compared to baseline measurements. A significative proportion of patients achieved the minimum clinically detectable improvement, specifically 79% for NRS and 83% for WOMAC (19 and 20 patients, respectively). Conclusion Our data showed a significant efficacy of ultrasound guided HMWHA-CT, in patients with KOA and CPPD, thus making it reasonable to consider that the combination of HMWHA and CTP can provide a strong anti-inflammatory effect.